When government helped : learning from the successes and failures of the New Deal - Collins, Sheila D.; Goldberg, Gertrude S. (Oxford University Press, 2013)
The global financial crisis of 2007-2008 was the most severe since the Great Depression. This book is a systematic evaluation of the parallels between the Great Depression and the 2007-2008 global economic meltdown. Although many books have been written on this topic, the unique aspect of this book is the analysis of the positive and negative lessons for contemporary policy-making of the New Deal response to the crisis, through viewing both the New Deal and the recent economic crisis in combination with the environmental crises of both eras. Integrating a unique blend of disciplines, this volu.